Proceeding International Conference on Islamic Leadership-2 (iCiL-2) 2012 intellectuality and leadership of Muslim scholars in research, innovation and creativity in Asean region - Mohd Rushdan Mohd Jailani (Fakulti Kepimpinan dan Pengurusan, Universiti Sains Islam Malaysia, 2012)
This proceeding is a compilation of papers presented at the International Conference on Islamic Leadership-2 (ICIL-2) 2012 with the theme " Intellectuality and Leadership of Muslim Scholars in Research, Innovation and Creativity in ASEAN Region". Altogether, there are two plenary papers and 48 papers presented at the parallel sessions in this proceeding. The papers are grouped into 7 themes to reflects the topics and issues covered and discussed during the conference and a completion of papers presented in Arabic language.